2006
DOI: 10.1142/s0192415x06003886
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Electroacupuncture on Cerebral Blood Flow in Rats With and Without Cerebral Ischemia

Abstract: Electroacupuncture (EA) is widely used to treat disorders of the nervous system, such as stroke. The aim of the present study was to investigate the effect of EA on cerebral blood flow (CBF) in cerebral ischemic rats. We developed an animal model of cerebral ischemia (CI) by occluding the blood flow of both common carotid arteries in Sprague-Dawley (SD) rats; 2 or 15 Hz EA was applied to both Zusanli acupoints. The levels of nitric oxide (NO) in the peripheral blood and amounts of calcitonin gene-related pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…For example, the deficits in hippocampal LTP could be reversed by phosphodiesterase (PDE) inhibitors such as rolipram, which raises cAMP levels [16]. Numerous studies have demonstrated that acupuncture at ST36 acupoint possesses a neuroprotective effect by suppressing neuron apoptosis [17,18], improving neural plasticity [19], increasing cerebral blood flow, and improving microcirculation [20] in ischemic rat brains. Our previous work indicated that acupuncture at Tanzhong (CV17), Zhongwan (CV12), Qihai (CV6), Zusanli (ST36) and Xuehai (SP10) could improve cognitive impairment caused by multi-infarct dementia rats [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the deficits in hippocampal LTP could be reversed by phosphodiesterase (PDE) inhibitors such as rolipram, which raises cAMP levels [16]. Numerous studies have demonstrated that acupuncture at ST36 acupoint possesses a neuroprotective effect by suppressing neuron apoptosis [17,18], improving neural plasticity [19], increasing cerebral blood flow, and improving microcirculation [20] in ischemic rat brains. Our previous work indicated that acupuncture at Tanzhong (CV17), Zhongwan (CV12), Qihai (CV6), Zusanli (ST36) and Xuehai (SP10) could improve cognitive impairment caused by multi-infarct dementia rats [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that acupuncture at the Zusanli (ST36) acupoint possesses a neuroprotective effect by suppressing neuron apoptosis [21,22], improving neural plasticity [23], increasing cerebral blood flow, and improving microcirculation [24] in ischemic rat brains. Recently, acupuncture at the Zusanli acupoint has been shown to not only suppress ICH-induced apoptotic neuronal cell death [8] but also accelerate ICH-induced angiogenesis in rats [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that EA of hindlimb possesses a neuroprotective effect in animal models of epilepsy [6] and other animal models of brain disease [24,25]. It is also known that EA of hindlimb markedly improved blood supply and microcirculation in the cerebral tissues, which indicated that EA stimulation of hindlimb could alleviate hypoxia-ischemia-associated neuron loss and thus possess a neuroprotective effect [26,27]. Since supragranular MFS is largely attributed to loss of the gran-ule cells in the dentate gyrus [28], EA stimulation of hindlimb may suppress MFS through its neuroprotective effect, finally contributing to the antiepileptic effect.…”
Section: Discussionmentioning
confidence: 99%